Pengaruh Pemberian Konsentrasi Air Fermentasi Dari Limbah Organik Terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) Varietas Mercy F1 - Putri, Nadila Aisha; Rahmi, Hayatul (JURNAL AGROPLASMA, 2023)
Cucumber (Cucumis sativus L) is one of the most widely consumed horticultural product in Indonesia. The use of organic matter is one of the efforts to meet the nutritional needs that will be absorbed by plants and increase soil fertility. The purpose of this study was to provide information on the best concentration of fermented water from organic waste on the growth and yield of cucumber (Cucumis sativus L.) Mercy F1 variety. This research was conducted for three months, from February to March 2022 in Sukaluyu Village, Telukjambe Timur District, Karawang Regency, West Java Province, Indonesia. This research method used an experimental method with a single factor randomized block design (RAK). The number of treatments was 8, each of which was repeated 4 times, so there were 32 experimental units. The treatments were A0 (0 ml/l), A1 (100 ml/l), A2 (200 ml/l), A3 (300 ml/l), A4 (400 ml/l), A5 (500 ml/l ), A6 (NASA POC), and A7 (NPK Fertilizer). The results showed that the application of giving the concentration of fermented water from organic waste did not significantly affect the growth and yield of cucumber (Cucumis sativus L.) Mercy F1 variety. Keywords: Cucumber, Fermented Water, Organic Waste.